Pengaruh Waktu Kneading Terhadap Efektifitas Enkapsulasi Molekul Minyak Esensial Daun Ruku-Ruku (Ocinum tenuiflorum) pada β- Siklodektrin (β-CD) - Elfanny Delvia; Sri Benti Etika; Hesty Parbuntari (Jurnal Periodic Jurusan Kimia UNP, 2021)
The leaves of ruku-ruku (Ocinum Tenuiflorum contain secondary metabolites in the form of essential oils which can be used as medicinal compounds. Ruku- ruku essential oil  (Ocinum Tenuiflorum) is useful as an aromatheraphy, cosmetic ingredient, antibacterial, anti-inflammatory and as an anticancer, however essential oils are unstable, susceptible to high temperatures, and easily oxidized. For that we need encapsulation with a coating material that can provide a solution to these problems. β-siklodekstrin is a good coating for essential oil encapsulation. Research has been conducted to prevent the disruption of inclusion complexes with vrying stirring time. FT-IR analysis showed that there was a shift in wavelength between the parent molecule β-siklodekstrin and the inclusion complex, namely an increase in the inclusion complex resulting in a widening of the absorbance band. The stability of the inclusion complexes formed can be seen from the melting point of the inclusion complex which is almost close to the melting of β-siklodekstrin cyclodextrin (> 290ºC), the melting point of the inclusion complex with variations in the stirring time of 15 minutes, 30 minutes, and 45 minutes respectively  287ºC, 280ºC, dan s278ºC. This high melting points indicates a stable inclusion complex that does not break down easily.